2021
DOI: 10.1186/s13584-021-00467-9
|View full text |Cite|
|
Sign up to set email alerts
|

Ethnic and minority group differences in engagement with COVID-19 vaccination programmes – at Pandemic Pace; when vaccine confidence in mass rollout meets local vaccine hesitancy

Abstract: Israel, the UK, the USA, and some other wealthier countries lead in the implementation of COVID-19 vaccine mass vaccination programmes. Evidence from these countries indicates that their ethnic minorities could be as disproportionately disadvantaged in COVID-19 vaccines roll-out as they were affected by COVID-19-related serious illnesses. Their disadvantage is linked to their lower social status and fewer social goods compared with dominant population groups.Albeit limited by methodology, early studies attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
1
29
0
1
Order By: Relevance
“…For example, Nikovolski et al [15] found that negative stories on vaccine adverse effects circulating online were associated with an increased unwillingness for people to get vaccinated for COVID-19. The study [41] showed how information reliability resulted in some Arab ethnic community members believing that the COVID-19 vaccine contained non-Halal or alcohol-based components, thus in turn negatively affecting the COVID-19 vaccine uptake. A study by Gatwood et al, on matters concerning how political ideology impacts COVID-19 vaccine hesitancy, states COVID-19 vaccine hesitancy was more likely among those with more moderate or conservative political leanings, Black Americans and, residents of nonmetropolitan areas [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Nikovolski et al [15] found that negative stories on vaccine adverse effects circulating online were associated with an increased unwillingness for people to get vaccinated for COVID-19. The study [41] showed how information reliability resulted in some Arab ethnic community members believing that the COVID-19 vaccine contained non-Halal or alcohol-based components, thus in turn negatively affecting the COVID-19 vaccine uptake. A study by Gatwood et al, on matters concerning how political ideology impacts COVID-19 vaccine hesitancy, states COVID-19 vaccine hesitancy was more likely among those with more moderate or conservative political leanings, Black Americans and, residents of nonmetropolitan areas [32].…”
Section: Discussionmentioning
confidence: 99%
“…Hesitancy among several Muslim and other religious groups was also observed because of the perception that pork gelatine was one of the ingredients in the COVID-19 vaccine [44]. Among Arabs and ethnic minorities in a study conducted in Israel, UK, and the US, it was found that along with family and friends, religious leaders are relatively high influencers in vaccine decision-making [41].…”
Section: Discussionmentioning
confidence: 99%
“…There have been instances of vaccine complacency in the past against other vaccination drives [ 8 ]. Vaccine complacency for the same vaccine differs from region to region at the same or different periods of time depending on socio-behavioural factors.…”
Section: Main Textmentioning
confidence: 99%
“…Vaccine acceptance and hesitancy are complex in nature and vary across time, place, and culture [5] , [6] , [7] , [8] . However, some common factors were identified across studies conducted in 2020 in anticipation of and in the early days of the COVID-19 vaccine approval and implementation.…”
Section: Introductionmentioning
confidence: 99%